(untitled) (International Journal of Environmental Sciences, 2025)
This study aims to analyze how popular culture, disseminated through television and social media, transforms individual lives, specifically within the context of fashion-themed reality shows in Turkey. In this regard, the study focuses on the case of Nihal Candan, a contestant on the fashion competition show “İşte Benim Stilim” broadcast on TV8 in 2015, who later passed away due to anorexia. The research investigates how popular culture, mediated through television and social media, shapes perceptions and affects individual lives using content analysis methodology. Nihal Candan’s media-driven visibility, her constructed self-perception, and her life that ended in tragedy are examined to reveal the transformative power of the culture industry on the individual. Utilizing qualitative research methods, the study analyzes the formal characteristics of the television show, its representational strategies, and the cultural discourses embedded within it. The findings demonstrate that the language used in televised popular culture and female representations involves ideological direction and encourages conformity to certain social norms. In this context, the culture industry not only shapes the intellectual and emotional world of individuals but also suppresses originality and weakens critical thinking.